Secondary sodium battery, preparation method and battery pack
By employing a carbon skeleton and functional material modification layers in sodium-ion batteries, the battery structure is optimized, solving the problems of low energy density and safety risks, and achieving improved high energy density and safety, making it suitable for renewable energy, consumer electronics, and electric vehicles.
Patent Information
- Application Number
- CN202410454795.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-16
- Publication Date
- 2025-10-24
AI Technical Summary
Existing sodium-ion batteries have a low energy density, which limits their use in high-end applications, and the sodium metal produced at the negative electrode during charging poses a safety risk.
A modification layer consisting of a carbon skeleton and functional materials is used to provide active sites for sodium deposition. Combined with polymer binders and membrane design, the battery structure is optimized to improve energy density and reduce safety risks.
This improves the energy density of sodium-ion batteries, meeting the needs of renewable energy, consumer electronics, and electric vehicles, while reducing safety risks during charging.
Smart Images

Figure CN120834265A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of batteries, and particularly relates to a secondary sodium battery, a preparation method and a battery pack. BACKGROUND
[0002] Under the current energy environment, energy density has become a serious challenge faced by lithium-ion battery technology. In large-scale energy storage systems, electric vehicles and other high-energy-density applications, the energy density limitation of lithium-ion batteries has become an important problem. In addition, the limited nature of lithium resources has also led people to focus on alternative battery technologies. Therefore, in order to overcome this limitation and seek more potential alternatives, researchers have begun to focus on sodium-ion batteries.
[0003] The advantage of sodium-ion batteries is that the raw materials used are relatively inexpensive and widely available. They may have greater economic advantages in large-scale energy storage systems, especially under the social demand of improving energy sustainable utilization. However, the current sodium-ion batteries still face the problem of low energy density, which limits their use in some high-end applications. The low energy density of sodium-ion batteries is mainly due to the limitations of electrode materials and battery design. The current sodium-ion batteries also have the problem of low energy density due to the characteristics of the electrochemical reaction. Therefore, we need to find new electrode materials and electrolytes, as well as design new battery system structures, to improve the energy density of sodium-ion batteries and enable them to be used in a wider range of applications.
[0004] Therefore, how to improve the low energy density of sodium-ion batteries has become a problem that needs to be solved. SUMMARY
[0005] The present application embodiment aims at the problem of low energy density of existing sodium-ion batteries, and proposes a secondary sodium battery, a preparation method, a battery pack and an application, which improves the energy density of sodium-ion batteries and reduces the safety risk of sodium metal produced by the negative electrode during charging.
[0006] To achieve the above-mentioned purpose, the technical solutions adopted by the embodiments of the present application are as follows:
[0007] In a first aspect, the present application embodiment provides a secondary sodium battery, which comprises a positive electrode end, a negative electrode end and a separator, the negative electrode end comprises a current collector and a modification layer, the modification layer is used to provide active sites for sodium deposition, and the modification layer comprises a carbon skeleton, a functional material and a polymer binder, the separator is arranged between the positive electrode end and the negative electrode end, and the separator is used to store electrolyte.
[0008] In a possible implementation manner, the surface loading in the modification layer is between 0.05-2.0 mg / cm 2and the negative end dry film thickness is between 10-50 μm.
[0009] In a possible implementation, the carbon skeleton comprises one or more of nano-porous carbon, graphite, carbon black, carbon nanotube, hard carbon, soft carbon, activated carbon, carbon aerogel, mesoporous carbon, mesocarbon microbead and graphene.
[0010] In a possible implementation, the carbon skeleton at least meets one or more of the following conditions: the mass ratio of the carbon skeleton in the modification layer is 40wt%-99wt%; the volume ratio of the carbon skeleton in the modification layer is 80%-99%; the particle size D50 of the carbon skeleton ranges from 1-20 μm.
[0011] In a possible implementation, the modification layer further comprises a functional material for reducing the reaction overpotential, and the functional material comprises one or more of a metal and a fluoride, oxide, halide, sulfide, phosphide, boride, selenide, hydride and nitride of the metal; and the metal comprises Mg, Zn, Bi, Sn, Ge, Si, Pb, Sb, In, Ca, Ni, Ga, Ti.
[0012] In a possible implementation, the functional material at least meets one or more of the following conditions: the mass ratio of the functional material in the modification layer is 0.1wt%-49wt%; the volume ratio of the functional material in the modification layer is 0.01%-19%.
[0013] In a possible implementation, the binder comprises one or more of lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, sodium carboxymethyl cellulose, polyvinylidene fluoride, sodium alginate, butadiene styrene rubber, guar gum, xanthan gum, tragacanth gum, gum arabic, polyacrylonitrile and acrylonitrile multi-polymer; and the mass ratio of the binder in the modification layer is 0.1wt%-40wt%.
[0014] In a possible implementation, the negative electrode of the secondary sodium battery provides a capacity not higher than 20% of the battery capacity; and the current collector comprises one or more of Al, Cu, Ti, Ni, stainless steel, carbon cloth, carbon felt, carbon paper and carbon aerogel.
[0015] In a second aspect, an embodiment of the present application provides a preparation method of a secondary sodium battery, comprising:
[0016] The positive electrode active material, the conductive agent and the binder are mixed and stirred according to a preset first mass ratio, a solvent is added, and a positive electrode slurry with uniform distribution is prepared; the positive electrode slurry is uniformly coated on two surfaces of a positive electrode current collector aluminum foil, dried at a first preset temperature, and then cold-pressed to obtain a positive electrode end coated with a double-sided positive electrode slurry.
[0017] After the modification layer material is mixed and stirred according to a preset second mass ratio, a solvent is added to prepare a negative electrode slurry; the negative electrode slurry is uniformly coated on two surfaces of the current collector, and is dried at a second preset temperature to obtain a negative electrode terminal coated with the negative electrode slurry on both surfaces;
[0018] The positive electrode terminal, the separator and the negative electrode terminal are sequentially stacked in order, with the separator being located between the positive electrode terminal and the negative electrode terminal, and the positive electrode terminal and the negative electrode terminal being stacked or wound respectively to obtain an electrode assembly; the electrode assembly is loaded into a shell assembly, and is dehydrated again, and the prepared electrolyte is injected to obtain a secondary sodium battery.
[0019] In a third aspect, an embodiment of the present application provides a battery pack comprising the secondary sodium battery according to the first aspect of the present application.
[0020] The embodiment of the present application provides a secondary sodium battery, and the capacity of the battery is derived from a positive electrode, and a negative electrode almost does not provide capacity, and the capacity of the negative electrode is not higher than 20% of the capacity of the battery. The secondary sodium battery comprises a positive electrode terminal, a negative electrode terminal and a separator. The positive electrode terminal comprises a positive electrode active material. The negative electrode terminal comprises a current collector and a modification layer. The modification layer is used for providing active sites for sodium deposition. The modification layer comprises a carbon skeleton, a functional material and a polymer binder. The separator is arranged between the positive electrode terminal and the negative electrode terminal, and keeps electrolyte. Compared with the problem of low energy density of a sodium ion battery in the prior art, the present application provides a new electrode material and an electrolyte, improves the energy density of the sodium ion battery, and reduces the safety risk of sodium metal generated in the negative electrode in the charging process.
[0021] The battery pack of the secondary sodium battery provided by the embodiment of the present application has the same advantages as the secondary sodium battery, and can meet the use requirements in the fields of renewable energy, consumer electronics and electric vehicles. BRIEF DESCRIPTION OF DRAWINGS
[0022] Figure 1 The secondary sodium battery is prepared by the embodiment 1 of the present application. DETAILED DESCRIPTION
[0023] The following non-limiting examples can make those skilled in the art more fully understand the present application, but do not limit the present application in any way. The following content is only an exemplary description of the scope of the present application, and those skilled in the art can make various changes and modifications to the present application according to the disclosed content, and it should also belong to the scope of the present application.
[0024] When embodiments recite a numerical range, it is contemplated that any number within that range, as well as the two endpoints, is also specifically contemplated. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs.
[0025] The application will be further described in the general context of particular embodiments. The various chemical reagents used in the embodiments of the application are obtained from conventional commercial sources unless otherwise specified.
[0026] In the current energy environment, energy density has become a serious challenge for lithium-ion battery technology. The energy density limitation of lithium-ion batteries has become an important issue in large-scale energy storage systems, electric vehicles, and other high-energy density applications. In addition, the limited nature of lithium resources has also led people to focus on alternative battery technologies. Therefore, to overcome this limitation and seek more potential alternatives, researchers have begun to focus on sodium-ion batteries.
[0027] The advantage of sodium-ion batteries is that the raw materials used are relatively inexpensive and widely available. They may have greater economic advantages in large-scale energy storage systems, especially under the social demand to improve energy sustainability. However, current sodium-ion batteries still face the problem of low energy density, which limits their use in some high-end applications. The low energy density of sodium-ion batteries is mainly due to the limitations of electrode materials and battery design. The current sodium-ion battery also has the problem of low energy density due to the characteristics of the electrochemical reaction. Based on this, we need to find new electrode materials and electrolytes, as well as design new battery system structures, to improve the energy density of sodium-ion batteries and enable them to be used in a wider range of applications.
[0028] The huge advantages of anode-free sodium batteries in energy density and cost make them have a huge application market. However, there are still problems to be solved: the cycle performance must be greatly improved in order to transition from laboratory scale to industrial scale; the safety risk of sodium metal produced by the negative electrode during charging needs to be reduced; in order to adapt to the volume change during charging and discharging, battery components suitable for anode-free sodium batteries need to be customized, which seriously hinders the improvement of sodium battery energy density and its practical application.
[0029] To address the above technical issues, the present application provides a secondary sodium battery. It comprises: a positive terminal comprising a positive electrode active material; a negative terminal comprising a current collector and a modified layer comprising a carbon skeleton and a polymer binder, providing active sites for sodium deposition; and a separator disposed between the positive and negative terminals to retain the electrolyte. This battery addresses the low energy density of existing sodium-ion batteries and reduces the safety risks posed by sodium metal generated at the negative electrode during charging.
[0030] Among them, the secondary sodium battery in the embodiment of the present invention includes a positive terminal, a negative terminal and a separator, the negative terminal includes a current collector and a modified layer, the modified layer is used to provide an active site for sodium deposition, the modified layer includes a carbon skeleton, a functional material and a polymer binder, the separator is arranged between the positive terminal and the negative terminal, and the separator is used to store the electrolyte. The surface loading in the modified layer is between 0.05-2.0 mg / cm 2 The negative terminal dry film thickness is between 10-50 μm. The carbon skeleton satisfies one or more of the following conditions: the carbon skeleton accounts for 40% to 99% by weight of the modified layer; the carbon skeleton accounts for 80% to 99% by volume of the modified layer; and the carbon skeleton has a particle size D50 in the range of 1-20 μm. The modified layer also includes a functional material, which is used to reduce the reaction overpotential. The functional material includes one or more of metals and their fluorides, oxides, halides, sulfides, phosphides, borides, selenides, hydrides, and nitrides. The metals include Mg, Zn, Bi, Sn, Ge, Si, Pb, Sb, In, Ca, Ni, Ga, and Ti. The functional material satisfies at least one of the following conditions: the functional material accounts for 0.1% to 49% by weight of the modified layer; and the functional material accounts for 0.01% to 19% by volume of the modified layer. The binder comprises one or more of lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, sodium carboxymethyl cellulose, polyvinylidene fluoride, sodium alginate, styrene-butadiene rubber, guar gum, xanthan gum, tragacanth gum, gum arabic, polyacrylonitrile, and acrylonitrile multipolymer; the binder accounts for 0.1% to 40% by weight of the modified layer. The negative electrode of the secondary sodium battery provides a capacity no greater than 20% of the battery capacity; and the current collector comprises one or more of aluminum, copper, titanium, nickel, stainless steel, carbon cloth, carbon felt, carbon paper, and carbon aerogel.
[0031] The present invention is further described in detail below with reference to the following embodiments.
[0032] Example 1
[0033] This embodiment provides a method for preparing secondary sodium, comprising:
[0034] Preparation of positive electrode tab
[0035] The positive electrode tab was prepared as follows. The positive electrode active material (sodium iron pyrophosphate in this example), conductive agent Super P, and binder polyvinylidene difluoride (PVDF) were weighed according to the mass ratio of 96:1.0:3.0 (e.g., 96 g of sodium iron pyrophosphate, 1.0 g of Super P, and 3.0 g of PVDF), and then added to a 2-L stirring tank for mechanical mixing. N-methylpyrrolidone (NMP) was added as a solvent to prepare a positive electrode slurry with a solid content of 75%. After stirring for 2 h, the slurry was uniformly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12 μm. The coated positive electrode tab was dried at 100 °C. The surface loading of sodium iron pyrophosphate on the positive electrode tab was 13.0 mg / cm 2 The thickness of the dried positive electrode tab was measured to be 120 μm. The above steps were repeated on the other surface of the positive electrode tab to obtain a positive electrode tab coated with sodium iron pyrophosphate on both surfaces. The positive electrode tab was cold-pressed and cut into a 56 mm x 43 mm size for use.
[0036] Preparation of negative electrode tab
[0037] The ordered mesoporous carbon CMK-3, binder sodium carboxymethyl cellulose (CMC), and butadiene-styrene rubber (SBR) were weighed according to the mass ratio of 85.0:5.0:10.0 (e.g., 85.0 g of ordered mesoporous carbon CMK-3, 5.0 g of CMC, and 10.0 g of SBR), and then added to a 2-L stirring tank for mechanical mixing. Deionized water was added as a solvent to prepare a slurry with a solid content of 45%. After stirring for 2 h, the slurry was uniformly coated on one surface of a negative electrode current collector aluminum foil with a thickness of 12 μm. The coated negative electrode tab was dried at 80 °C. The surface loading of the ordered mesoporous carbon CMK-3 modification layer on the negative electrode tab was 0.15 mg / cm 2 The thickness of the dried negative electrode tab was measured to be 20 μm. The above steps were repeated on the other surface of the negative electrode tab to obtain a negative electrode tab coated with ordered mesoporous carbon CMK-3 on both surfaces. The coated negative electrode tab was cut into a 58 mm x 45 mm size for use. Unlike the positive electrode tab, the negative electrode tab with the modification layer was not subjected to a rolling operation.
[0038] Preparation of electrolyte
[0039] In a glove box under dry argon atmosphere (H2O < 0.01 ppm, O2 < 0.01 ppm), organic solvents ethylene glycol dimethyl ether, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether after water removal by molecular sieves were mixed in a volume ratio of 1:1:1, then sodium salt sodium hexafluorophosphate (NaPF6) was added to the mixed organic solvent to dissolve and mix uniformly, to obtain an electrolyte with a sodium salt concentration of 1 mol / L.
[0040] Separator
[0041] Polypropylene film with a thickness of 15 μm (provided by Celgard) was used. The packaging material was 113 μm aluminum-plastic composite film.
[0042] Preparation of secondary sodium battery
[0043] The above-prepared positive electrode end, separator, and negative electrode end were sequentially stacked in order, with the separator between the positive electrode end and the negative electrode end to serve as an isolation function. The electrode assembly / battery pack was obtained by winding / stacking. The electrode assembly was loaded into an aluminum-plastic composite film and heated to remove moisture. The prepared electrolyte was injected, and the soft-pack secondary battery was obtained after vacuum packaging, standing, formation, shaping, and other processes, as shown in Figure 1 .
[0044] Example 2
[0045] In this example, the positive electrode end, electrolyte, separator, and secondary sodium battery were prepared as in Example 1, except that the negative electrode end was prepared as follows:
[0046] Ordered mesoporous carbon CMK-3, silicon nitride, sodium carboxymethyl cellulose CMC, and styrene-butadiene rubber SBR were weighed according to a mass ratio of 80.0:10.0:3.0:7.0 (e.g., 80.0 g of ordered mesoporous carbon CMK-3, 10.0 g of silicon nitride, 3.0 g of CMC, and 7.0 g of SBR), added to a 2 L stirring tank, and mechanically mixed. Deionized water was added as a solvent to prepare a slurry with a solid content of 40%, and the slurry was stirred for 2 hours to achieve uniform dispersion. The stirred slurry of the modification layer was uniformly coated on one surface of a current collector aluminum foil with a thickness of 12 μm, and dried at 80°C to obtain a pole piece coated with a single-sided porous modification layer of ordered mesoporous carbon CMK-3 and silicon nitride, with a surface loading of 0.16 mg / cm 2 . The thickness of the dry film of the negative electrode end was measured to be 20 μm. Then, the above steps were repeated on the other surface of the pole piece to obtain a pole piece coated with a double-sided porous composite modification layer slurry. After coating, the pole piece was cut into a specification of 58 mm x 45 mm for use. Unlike the positive electrode piece, the pole piece with the modification layer was not subjected to a rolling operation.
[0047] Example 3
[0048] In this embodiment, the preparation of the positive electrode, electrolyte, separator and secondary sodium battery is the same as in Example 1, except that the preparation of the negative electrode is different from that in Example 1:
[0049] The ordered mesoporous carbon CMK-3, silicon nitride, sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR, wherein the particle size D50 of the ordered mesoporous carbon CMK-3 is 20 μm, are weighed according to the mass ratio of 80.0:10.0:3.0:7.0 (for example, 80.0 g of ordered mesoporous carbon CMK-3, 10.0 g of silicon nitride, 3.0 g of CMC and 7.0 g of SBR), then added into a 2L stirring tank for mechanical mixing, deionized water is added as a solvent, and a slurry with a solid content of 40% is prepared, and stirred for 2 hours to make it uniformly dispersed. The uniformly stirred slurry is uniformly coated on one surface of the current collector aluminum foil with a thickness of 12 μm, and dried at 80°C to obtain a single-sided coated porous modified layer electrode sheet, and the surface loading of the ordered mesoporous carbon CMK-3 and silicon nitride modified layer is 0.5 mg / cm 2 The thickness of the dry film of the negative electrode is measured to be 50 μm. Then, the above steps are repeated on the other surface of the electrode sheet to obtain a double-sided coated porous composite modified layer slurry electrode sheet. After coating, it is cut into a specification of 58 mm x 45 mm for use. Unlike the positive electrode sheet, the modified layer-containing electrode sheet does not undergo a rolling operation.
[0050] Example 4
[0051] In this embodiment, the preparation of the positive electrode, electrolyte, separator and secondary sodium battery is the same as in Example 1, except that the preparation of the negative electrode is different from that in Example 1:
[0052] The ordered mesoporous carbon CMK-3, silicon nitride, sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR, wherein the particle size D50 of the ordered mesoporous carbon CMK-3 is 10 μm, are weighed according to the mass ratio of 80.0:10.0:3.0:7.0 (for example, 80.0 g of ordered mesoporous carbon CMK-3, 10.0 g of silicon nitride, 3.0 g of CMC and 7.0 g of SBR), then added into a 2L stirring tank for mechanical mixing, deionized water is added as a solvent, and a slurry with a solid content of 30% is prepared, and stirred for 2 hours to make it uniformly dispersed. The uniformly stirred slurry is uniformly coated on one surface of the negative current collector aluminum foil with a thickness of 12 μm, and dried at 80°C to obtain a single-sided coated porous modified layer electrode sheet, and the surface loading of the ordered mesoporous carbon CMK-3 and silicon nitride modified layer is 0.1 mg / cm 2The thickness of the dry film of the negative electrode end was measured to be 10 μm. Then, the above steps were repeated on the other surface of the negative electrode end, and a pole piece coated with a porous composite modification layer slurry on both surfaces was obtained. After the coating was completed, it was cut into a 58 mm x 45 mm specification for use. Unlike the positive electrode piece, the negative electrode piece was not subjected to a rolling operation.
[0053] Example 5
[0054] In this example, the preparation of the positive electrode end, electrolyte, separator, and secondary sodium battery was the same as in Example 1, except that the preparation of the negative electrode end was different from that in Example 1:
[0055] Ordered mesoporous carbon CMK-3, silicon nitride, carboxymethyl cellulose sodium CMC, and styrene-butadiene rubber SBR were weighed according to a mass ratio of 40.0:40.0:5.0:15.0 (e.g., 40.0 g of ordered mesoporous carbon CMK-3, 40.0 g of silicon nitride, 5.0 g of CMC, and 15.0 g of SBR), and then added to a 2 L stirring tank for mechanical mixing. Deionized water was added as a solvent to prepare a slurry with a solid content of 30%, and the slurry was stirred for 2 hours to make it uniformly dispersed. The uniformly stirred slurry was uniformly coated on one surface of a negative current collector aluminum foil with a thickness of 12 μm, and then dried at 80°C to obtain a pole piece coated with a porous modification layer on one surface, with a surface loading of ordered mesoporous carbon CMK-3 and silicon nitride modification layer of 0.05 mg / cm 2 The thickness of the dry film of the negative electrode end was measured to be 10 μm. Then, the above steps were repeated on the other surface of the negative electrode end, and a pole piece coated with a porous composite modification layer slurry on both surfaces was obtained. After the coating was completed, it was cut into a 58 mm x 45 mm specification for use. Unlike the positive electrode piece, the negative electrode piece was not subjected to a rolling operation.
[0056] Example 6
[0057] In this example, the preparation of the positive electrode end, electrolyte, separator, and secondary sodium battery was the same as in Example 1, except that the preparation of the negative electrode end was different from that in Example 1:
[0058] The ordered mesoporous carbon CMK-3, silicon nitride, sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR, wherein the particle size D50 of the ordered mesoporous carbon CMK-3 is 20 μm, are weighed according to the mass ratio of 99.00:0.90:0.05:0.05 (for example, ordered mesoporous carbon CMK-3 99.00 g, silicon nitride 0.90 g, CMC 0.05 g, SBR 0.05 g), then added into a 2 L stirring tank for mechanical mixing, deionized water is added as a solvent, and a slurry with a solid content of 30% is prepared, and stirred for 2 hours to make it uniformly dispersed. The uniformly stirred slurry is uniformly coated on one surface of an aluminum foil negative current collector with a thickness of 12 μm, dried at 80°C, and a single-side coated porous modified layer electrode sheet is obtained, and the surface loading of the ordered mesoporous carbon CMK-3 and silicon nitride modified layer is 1.0 mg / cm 2 , and the thickness of the negative electrode dry film is measured to be 50 μm. Then, the above steps are repeated on the other surface of the negative electrode, and a double-side coated porous composite modified layer slurry electrode sheet is obtained. After coating, it is cut into a specification of 58 mm x 45 mm for use. Unlike the positive electrode sheet, the negative electrode sheet does not undergo a rolling operation.
[0059] Example 7
[0060] In this embodiment, the positive electrode, electrolyte, separator and secondary sodium battery are prepared as in Example 1, and the negative electrode is prepared differently from Example 1.
[0061] The ordered mesoporous carbon CMK-3, silicon nitride, sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR, wherein the particle size D50 of the ordered mesoporous carbon CMK-3 is 10 μm, are weighed according to the volume ratio of 80.0:19.0:0.5:0.5 (for example, ordered mesoporous carbon CMK-3 80.0 cm 3 , silicon nitride 19.0 cm 3 , CMC 0.5 cm 3 , SBR 0.5 cm 3 ), then added into a 2 L stirring tank for mechanical mixing, deionized water is added as a solvent, and a slurry with a solid content of 30% is prepared, and stirred for 2 hours to make it uniformly dispersed. The uniformly stirred slurry is uniformly coated on one surface of an aluminum foil negative current collector with a thickness of 12 μm, dried at 80°C, and a single-side coated porous modified layer electrode sheet is obtained, and the surface loading of the ordered mesoporous carbon CMK-3 and silicon nitride modified layer is 0.05 mg / cm 2 , and the thickness of the negative electrode dry film is measured to be 10 μm. Then, the above steps are repeated on the other surface of the negative electrode, and a double-side coated porous composite modified layer slurry electrode sheet is obtained. After coating, it is cut into a specification of 58 mm x 45 mm for use. Unlike the positive electrode sheet, the negative electrode sheet does not undergo a rolling operation.
[0062] Example 8
[0063] In this embodiment, the preparation of the positive electrode, electrolyte, separator and secondary sodium battery is the same as in Example 1, except that the preparation of the negative electrode is different from that in Example 1:
[0064] The ordered mesoporous carbon CMK-3, silicon nitride, sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR, wherein the particle size D50 of the ordered mesoporous carbon CMK-3 is 10 μm, are weighed according to the volume ratio of 99.00:0.01:0.29:0.70 (for example, 99.00 cm 3 , silicon nitride 0.01 cm 3 , CMC 0.29 cm 3 , SBR 0.70 cm 3 ), and then added into a 2L stirring tank for mechanical mixing, deionized water is added as a solvent, and a slurry with a solid content of 30% is prepared, and stirred for 2 hours to make it uniformly dispersed. The stirred slurry is uniformly coated on one surface of the negative electrode current collector aluminum foil with a thickness of 12 μm, dried at 80°C, and a single-sided coated porous modified layer electrode sheet is obtained, the surface ordered mesoporous carbon CMK-3 and silicon nitride modified layer has a surface loading of 2.0 mg / cm 2 , and the thickness of the dry film of the negative electrode is measured to be 50 μm. Then, the above steps are repeated on the other surface of the negative electrode, and a double-sided coated porous composite modified layer slurry electrode sheet is obtained. After coating, it is cut into a specification of 58 mm x 45 mm for use. Unlike the positive electrode sheet, the negative electrode sheet does not undergo a rolling operation.
[0065] Example 9
[0066] In this embodiment, the preparation of the positive electrode, electrolyte, separator and secondary sodium battery is the same as in Example 1, except that the preparation of the negative electrode is different from that in Example 1:
[0067] The ordered mesoporous carbon CMK-3, silicon nitride, sodium carboxymethyl cellulose CMC and styrene-butadiene rubber SBR, wherein the particle size D50 of the ordered mesoporous carbon CMK-3 is 10 μm, are weighed according to the mass ratio of 59.9:0.1:20.0:20.0 (for example, 59.9 g of ordered mesoporous carbon CMK-3, 0.1 g of silicon nitride, 20.0 g of CMC, and 20.0 g of SBR), and then added into a 2L stirring tank for mechanical mixing, deionized water is added as a solvent, and a slurry with a solid content of 30% is prepared, and stirred for 2 hours to make it uniformly dispersed. The stirred slurry is uniformly coated on one surface of the negative electrode current collector aluminum foil with a thickness of 12 μm, dried at 80°C, and a single-sided coated porous modified layer electrode sheet is obtained, the surface ordered mesoporous carbon CMK-3 and silicon nitride modified layer has a surface loading of 0.1 mg / cm 2The thickness of the dry film of the negative electrode end was measured to be 15 pm. Then, the above steps were repeated on the other surface of the negative electrode end, and a pole piece coated with a porous composite modification layer slurry on both sides was obtained. After the coating was completed, it was cut into a 58 mm x 45 mm specification for use. Unlike the positive electrode piece, the negative electrode piece did not undergo a rolling operation.
[0068] Example 10
[0069] In this embodiment, the positive electrode end, electrolyte, separator, and preparation of the secondary sodium battery were the same as in Example 1. Unlike Example 1, the negative electrode end was prepared as follows:
[0070] Ordered mesoporous carbon CMK-3, silicon nitride, carboxymethyl cellulose sodium CMC, and styrene-butadiene rubber SBR were weighed according to a mass ratio of 50.0:49.0:0.5:0.5 (e.g., 50.0 g of ordered mesoporous carbon CMK-3, 49.0 g of silicon nitride, 0.5 g of CMC, and 0.5 g of SBR), and then added to a 2 L stirring tank for mechanical mixing. Deionized water was added as a solvent to prepare a slurry with a solid content of 30%, and the slurry was stirred for 2 hours to achieve uniform dispersion. The stirred slurry was uniformly coated on one surface of a negative current collector aluminum foil with a thickness of 12 pm, and then dried at 80°C to obtain a pole piece coated with a porous modification layer on one side, with a surface loading of ordered mesoporous carbon CMK-3 and silicon nitride modification layer of 0.2 mg / cm 2 The thickness of the dry film of the negative electrode end was measured to be 15 pm. Then, the above steps were repeated on the other surface of the negative electrode end, and a pole piece coated with a porous composite modification layer slurry on both sides was obtained. After the coating was completed, it was cut into a 58 mm x 45 mm specification for use. Unlike the positive electrode piece, the negative electrode piece did not undergo a rolling operation.
[0071] Comparative Example 1
[0072] In this embodiment, the positive electrode, electrolyte, and separator and the preparation of the secondary sodium battery were the same as in Example 1. Unlike Example 1, the negative electrode end was prepared as follows:
[0073] The AI current collector was directly cut into a 58 mm x 45 mm specification for use.
[0074] Comparative Example 2
[0075] In this embodiment, the positive electrode, electrolyte, and separator and the preparation of the secondary sodium battery were the same as in Example 1. Unlike Example 1, the negative electrode end was prepared as follows:
[0076] Silicon nitride, sodium carboxymethyl cellulose (CMC), and styrene butadiene rubber (SBR) were weighed according to a mass ratio of 96.0:1.0:3.0 (e.g., 96.0 g of silicon nitride, 1.0 g of CMC, and 3.0 g of SBR), added to a 2-L stirring tank, and mechanically mixed. Deionized water was added as a solvent to prepare a slurry having a solid content of 30%, and the slurry was stirred for 2 hours to uniformly disperse the components. The uniformly stirred slurry was uniformly coated on one surface of a current collector aluminum foil having a thickness of 12 μm, and dried at 80°C to obtain a functional material-coated electrode sheet having a surface loading of 0.6 mg / cm 2 The thickness of the negative electrode dry film was measured to be 20 μm. Thereafter, the above procedure was repeated on the other surface of the electrode sheet to obtain a functional material-coated electrode sheet having a double-sided coating. After the coating was completed, the electrode sheet was cut into a 58 mm x 45 mm size for use. Unlike the positive electrode sheet, the electrode sheet having the modification layer was not subjected to a roll pressing operation.
[0077] Comparative Example 3
[0078] In this example, the positive electrode, the electrolyte, and the separator, and the secondary sodium battery were prepared as in Example 1, except that the negative electrode was prepared as follows:
[0079] Sodium carboxymethyl cellulose (CMC) and styrene butadiene rubber (SBR) were weighed according to a mass ratio of 3:7 (e.g., 30 g of CMC and 70 g of SBR), added to a 2-L stirring tank, and mechanically mixed. Deionized water was added as a solvent to prepare a slurry having a solid content of 30%, and the slurry was stirred for 2 hours to uniformly disperse the components. The uniformly stirred slurry was uniformly coated on one surface of a current collector aluminum foil having a thickness of 12 μm, and dried at 80°C to obtain an adhesive-coated electrode sheet having a surface loading of 0.4 mg / cm 2 The thickness of the negative electrode dry film was measured to be 20 μm. Thereafter, the above procedure was repeated on the other surface of the electrode sheet to obtain an adhesive-coated electrode sheet having a double-sided adhesive layer. After the coating was completed, the electrode sheet was cut into a 58 mm x 45 mm size for use. Unlike the positive electrode sheet, the adhesive-coated electrode sheet was not subjected to a roll pressing operation.
[0080] In the case where the capacity provided by the negative electrode is less than 20% of the battery capacity, the modification layer thickness, average voltage, mass energy density, volume energy density, and 1000-cycle capacity retention rate of the modification layer of the examples and comparative examples are shown in Table 1:
[0081] Table 1
[0082]
[0083]
[0084] As can be seen from the example 1, the example 2 and the comparative examples 1-3, the average voltage, the mass / volume energy density and the cycle stability of the electrochemical device are all related to the modification layer, the CMK-3 carbon skeleton can provide the space required for sodium deposition, maintain the stability of the electrode structure and improve the cycle life of the battery; the functional Si3N4 material can reduce the sodium deposition overpotential, improve the voltage of the full battery, and the coordination of the two makes the energy density of the sodium battery reach 210 Wh / kg, the volume energy density is as high as 300 Wh / L, and the capacity retention rate is 95.1% after 1000 cycles.
[0085] As can be seen from the example 2 / example 3 and the example 4, the average voltage, the mass / volume energy density and the cycle stability of the electrochemical device are all related to the thickness of the modification layer, if the thickness of the modification layer is too thin, there may be aluminum leakage on the surface of the current collector, which is not enough to provide the space required for sodium deposition, and the cycle stability of the battery is reduced; if the thickness of the modification layer is too thick, the proportion of the non-active material is high, and the volume energy density is reduced. Therefore, the thickness of the modification layer needs to be optimized. For the modification layer containing the CMK-3 carbon skeleton and the functional Si3N4 material, the thickness is preferably about 20 um.
[0086] Through the design of the few negative electrodes and the composition / structure optimization, the mass energy density of the secondary sodium battery cell formed is 210 Wh / kg, which is more than 30% higher than that of the existing secondary sodium ion battery.
[0087] Finally, it should be noted that the above content is only used to illustrate the technical solutions of the present application, and is not a limitation on the protection scope of the present application. Simple modifications or equivalent replacements of the technical solutions of the present application made by those skilled in the art do not deviate from the essence and scope of the technical solutions of the present application.
[0088] The above only describes the preferred embodiments of the present application, and is not intended to limit the present application. Any modification, equivalent replacement and improvement made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A secondary sodium battery, characterized by, The secondary sodium battery comprises a positive electrode end, a negative electrode end and a separator, the negative electrode end comprises a current collector and a modification layer, the modification layer is used to provide active sites for sodium deposition, the modification layer comprises a carbon skeleton, a functional material and a polymer binder, and the separator is arranged between the positive electrode end and the negative electrode end and is used to store electrolyte. The carbon skeleton comprises one or more of nanoporous carbon, graphite, carbon black, carbon nanotubes, hard carbon, soft carbon, activated carbon, carbon aerogel, mesoporous carbon, mesocarbon microbeads and graphene.
2. The secondary sodium battery according to claim 1, characterized in that, The areal loading in the modification layer is between 0.05 and 2.0 mg / cm 2 and the negative end dry film thickness is between 10 and 50 μm.
3. The secondary sodium battery of claim 1, wherein, The carbon skeleton satisfies one or more of the following conditions:
4. The secondary sodium battery according to claim 3, characterized in that, The mass percentage of the carbon skeleton in the modification layer is 40% to 99% by weight; The volume percentage of the carbon skeleton in the modification layer is 80% to 99%; The particle size D50 of the carbon skeleton ranges from 1 to 20 microns. The functional material is used to reduce the reaction overpotential, and the functional material comprises one or more of a metal and fluorides, oxides, halides, sulfides, phosphides, borides, selenides, hydrides and nitrides of the metal; 5. The secondary sodium battery of claim 1, wherein, The metal comprises Mg, Zn, Bi, Sn, Ge, Si, Pb, Sb, In, Ca, Ni, Ga, Ti. The functional material satisfies one or more of the following conditions:
6. The secondary sodium battery of claim 5, wherein, The mass percentage of the functional material in the modification layer is 0.1% to 49% by weight; The volume percentage of the functional material in the modification layer is 0.01% to 19%. The binder comprises one or more of lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, sodium carboxymethyl cellulose, polyvinylidene fluoride, sodium alginate, butadiene styrene rubber, guar gum, xanthan gum, tragacanth gum, gum arabic, polyacrylonitrile and acrylonitrile multi-polymer, and the mass percentage of the binder in the modification layer is 0.1% to 40% by weight.
7. The secondary sodium battery of claim 1, wherein, The capacity provided by the negative electrode of the secondary sodium battery is not higher than 20% of the capacity of the battery; and the current collector comprises one or more of Al, Cu, Ti, Ni, stainless steel, carbon cloth, carbon felt, carbon paper and carbon aerogel.
8. The secondary sodium battery of claim 1, wherein, The method comprises:
9. A method of producing a secondary sodium battery as claimed in any one of claims 1 to 8, characterized in that, After mixing and stirring the positive electrode active material, the conductive agent and the binder according to a first preset mass ratio, a solvent is added to prepare a positive electrode slurry with uniform distribution; the positive electrode slurry is uniformly coated on two surfaces of the positive electrode current collector aluminum foil, dried at a first preset temperature, and then cold-pressed to obtain a positive electrode end coated with the double-sided positive electrode slurry; After mixing and stirring the modification layer material according to a second preset mass ratio, a solvent is added to prepare a negative electrode slurry; the negative electrode slurry is uniformly coated on two surfaces of the current collector, dried at a second preset temperature, and then cold-pressed to obtain a negative electrode end coated with the double-sided negative electrode slurry; The positive electrode end, the separator and the negative electrode end are sequentially stacked in order, with the separator between the positive electrode end and the negative electrode end, to obtain an electrode assembly; the electrode assembly is loaded into a shell assembly, and then dehydrated, and the prepared electrolyte is injected to obtain a secondary sodium battery. The secondary sodium battery comprises any one of the secondary sodium batteries according to claims 1 to 8.
10. A battery pack, characterized by,